Sensitivity and specificity of serum procalcitonin level compared to leucocyte count for diagnosis surgical site infection on patients undergoing major surgery in Dr. Sardjito General Hospital Yogyakarta - Umi Sholekah Intansari, Muhammad Sayuti Supomo (Universitas Gadjah Mada, 2013)
Surgical site infection (SSI) is one of the most serious complications on sugical procedure. However, its diagnosis is still based on the clinical and laboratory examination that take more time and less sensitive and specific. Therefore, early diagnosis that is more accurate and precise is needed. Some biomarker such as serum procalcitonin (PCT) is promoted for diagnosis SSI. The aim of the study was to evaluate the sensitivity and specificity of serum PCT compared with leucocyte for diagnosis SSI on patients undergoing major surgery. This was a descriptive analytical study with a prospective observational design. Patients who underwent a major surgery between October 30th and December 31rt, 2011 and fulfilled the inclusion and exclusion criteria were recruited. Clinical and laboratory examinations including leucocyte count were conducted presurgery. On 3rd day postsurgery, blood sample was taken for PCT and leucocyte count measurement. A blood bacterial culture was performed on patients suffering from SSI according to Centers for Disease Control (CDC) criteria. Patients were then followed until 30 days postsurgery. A total of 49 patients consisting of 22 men and 27 women were involved in this study. Surgical site infection was found in 16 patients consisting of 8 (50%) patients with clean surgical wound, 3 (19%) patients with clean surgical contamination wound, 4 (25%) patients with surgical contamination wound and 1 (6%) patient with dirty surgical wound. Furthermore, laboratory examination found that 9 patients had abnormal leucocyte with 5 of them suffering from SSI, whereas from 14 patients with serum PCT abnormal, 11 patients suffered from SSI. Diagnostic test showed that the sensitivity and specificity of serum PCT for diagnosis SSI were 68.75 and 90.90%, respectively, whereas the sensitivity and specificity of leucocyte were 31.25 and 87.87%, respectively. In conclusion, serum PCT has better sensitivity and specificity compared with leucocyte for the diagnosisof SSI in patients with major surgery. Â Â Keywords: procalcitoninserum - leucocyte Â - surgical site infection- diagnostic test - sensitivity â specificityÂ Â Â